Spatial and Temporal Dynamics of Inorganic Phosphate and Adenosine-5′-Triphosphate in the North Pacific Ocean - Björkman, Karin M.; Duhamel, Solange; Church, Matthew J.; Karl, David M. (Frontiers in Marine Science, 2018)
Temporal variability in dissolved inorganic, organic phosphate (Pi, DOP) and particulate phosphorus (PPO4) concentrations, and microbial utilization of Pi and dissolved adenosine-5’-triphosphate (DATP) was studied at Station ALOHA (22.75˚N, 158˚W) in the North Pacific Subtropical Gyre (NPSG) over a multi-year period. Spatial variability of the same properties was investigated along two transects, to and from Hawaii, that traversed the NPSG boundaries to the east (2014) and north (2016). Radiotracer techniques were employed to measure the turnover time of Pi and DATP pools to calculate Pi uptake rates and the Pi hydrolysis rates of DATP. Pi concentrations were more variable, both in time and space, than DOP, ranging two orders of magnitude compared to a factor of two for DOP. The DATP pool, while constituting on average <0.15% of the total DOP-P, was as dynamic as Pi (~1-200 pmol l-1), with lowest concentrations coinciding with Pi depletion. The Pi turnover times ranged from a few hours to several weeks, and were correlated with measured Pi concentrations (r=0.9; Station ALOHA, n=28; 2014, n=14; 2016, n=12). Pi uptake rates averaged 3.6±1.3 nmol-P d-1 (n=28: Station ALOHA), 9.2±4.7 nmol-P d-1, (n=15; 2014) and 5.1±2.5 nmol-P d-1, (n=12; 2016). The turnover time of the DATP pool was typically substantially shorter (0.4-5 days) than for the Pi-pool, and uptake rates ranged from 1-115 pmol l-1 d-1. However, at very low Pi and ATP concentrations, ATP turnover was longer than Pi turnover and ATP uptake rates lower. Total ATP hydrolysis was high along both transects, exceeding the ATP taken up by the microbial community, resulting in a net release of Pi into the ambient seawater. This net release was positively correlated to Pi concentration. The relative contribution by microbial size classes to total P-uptake depended on whether P was derived from ambient Pi or from DATP, with the <0.6>0.2 µm size class dominating the DATP uptake. Our results indicate that during Pi limiting conditions, regenerated P is rapidly consumed, and that Pi limitation occurs locally and transiently but does not appear to be the predominant condition in the upper water column of the NPSG.